Gut Microbiota Characteristics Are Associated With Severity of Acute Radiation-Induced Esophagitis - Lin, Ming-qiang; Wu, Ya-hua; Yang, Jun; Lin, Han-cui; Liu, Ling-yun; Yu, Yi-lin; Yao, Qi-wei; Li, Jian-cheng (Frontiers in Microbiology, 2022)
Background Acute radiation-induced esophagitis (ARIE) is one of the most debilitating complications in patients who receive thoracic radiotherapy, especially those with esophageal cancer (EC). There is little known about the impact of the characteristics of gut microbiota on the initiation and severity of ARIE. Materials and Methods Gut microbiota samples of EC patients undergoing radiotherapy (n = 7) or concurrent chemoradiotherapy (n = 42) were collected at the start, middle, and end of the radiotherapy regimen. Assessment of patient-reported ARIE was also performed. Based on 16S rRNA gene sequencing, changes of the gut microbial community during the treatment regimen and correlations of the gut microbiota characteristics with the severity of ARIE were investigated. Results There were significant associations of several properties of the gut microbiota with the severity of ARIE. The relative abundance of several genera in the phylum Proteobacteria increased significantly as mucositis severity increased. The predominant genera had characteristic changes during the treatment regimen, such as an increase of opportunistic pathogenic bacteria including Streptococcus. Patients with severe ARIE had significantly lower alpha diversity and a higher abundance of Fusobacterium before radiotherapy, but patients with mild ARIE were enriched in Klebsiella, Roseburia, Veillonella, Prevotella_9, Megasphaera, and Ruminococcus_2. A model combining these genera had the best performance in prediction of severe ARIE (area under the curve: 0.907). Conclusion The characteristics of gut microbiota before radiotherapy were associated with subsequent ARIE severity. Microbiota-based strategies have potential use for the early prediction of subsequent ARIE and for the selection of interventions that may prevent severe ARIE.